The Influence of STAD Learning Model on the Mathematics Learning Outcomes of Elementary School Students - Arrahim Arrahim; Rini Endah Sugiharti; Irine Victorynie; Ezha Zannati (Program Studi Tadris Matematika IAIN Salatiga, 2023)
The background of this research is motivated by low learning outcomes, low learning activity show by students and also math subjects are difficult to understand. To overcome these problems, it is necessary to apply Student Teams Achievement Division (STAD) learning model which is the simplest type of cooperative learning. This research purpose is to describe the results of learning mathematics in elementary schools using STAD model. The method that is used in this research is Systematic Literature Review (SLR). The data source that is used in this research is nine scientific journals related to mathematics learning outcomes using STAD model. The results show that the STAD model is very effective for mathematics learning outcomes on elementary school students. In the studies there is an effective influence and significance difference in upper grades (grade IV, V and VI) and lower grades (grade III) in learning outcomes for students who participate in using STAD model with average value of 81.15 and the percentage of completion reaches 95%.